Indigeneity, belonging, ‘madness’ and ‘corruption’: Brett Muvet and the white man’s identity crisis in post-2000 Zimbabwe - Albert Chibuwe (Taylor and Francis Group, 2023)
The article examines instances of white-talk in indigenous Shona language in post-2000 Zimbabwe. Grounded in concepts of whiteness, identity, citizenship and belonging, it interrogates discourses in videos produced and circulated by a white man – Brett Muvet – in Shona via YouTube. Through interrogating the ‘I’- ‘You’ and ‘Us’ – ‘Them’ dichotomies in his political commentary, the article interrogates how the white man seeks to re-insert himself in the national project. The findings demonstrate that for Brett whiteness is the point from which the world unfolds. His ‘talk’ demonstrates, regardless of claims to indigeneity, the white man’s problem of belonging in the post-colony.